Direct Comparison of Schlieren and Soot Foil Measurements of Detonation Cell Sizes - Carter, Mick; Blunck, David L. (Frontiers in Aerospace Engineering, 2022)
Detonation-based combustion cycles have the potential to have higher thermodynamic efficiencies than the more common deflagration-based combustion cycles because the pressure of the products is higher than that of the reactants. The geometry to which a detonation is confined can have a strong influence on the detonation’s behavior, or even prevent a detonation from occurring. A key measurement that can be used to design detonation-based engines is the cell size of the mixture. The cell size is a characteristic length scale of a chemical mixture. For the first time, this study compares two methods of collecting cell size measurements within a single tube. This approach controls for the effects of tube geometry and surface roughness, which may confound studies whose schlieren and soot foil measurements have been collected from different tubes. This study indicates that measurements taken using the two measurement techniques agree to within experimental uncertainty (a difference of 1.3 mm, or 7 %). Soot foil methods are generally preferable for detonation cell size measurements because soot foils provide larger triple point sample sizes per detonation and lower instrumentation costs relative to schlieren methods. Various sources of uncertainty are extensively analyzed and reported for the two techniques.